Chlamydia trachomatis Plasmid Protein pORF5 Up-Regulates ZFAS1 to Promote Host Cell Survival via MAPK/p38 Pathway - Wen, Yating; Chen, Hongliang; Luo, Fangzhen; Zhao, Lanhua; Shu, Mingyi; Su, Shengmei; Zhao, Yuqi; Huang, Qiulin; Li, Zhongyu (Frontiers in Microbiology, 2020)
Long non-coding RNAs (lncRNAs) have been demonstrated to play essential roles in many diseases. However, few studies have shown that lncRNAs take part in the pathogenesis of Chlamydia trachomatis (C. trachomatis). Here, we used a lncRNA microarray to detect the global lncRNA expression profiles in HeLa cells transfected with pORF5 plasmid protein, an important virulence factor for C. trachomatis. The differentially expressed lncRNAs and mRNAs screened by microarray were selected for validation by quantitative real-time PCR. The up-regulated lncRNA zinc finger antisense 1 (ZFAS1) was presumed to involved in MAPK pathways by bioinformatics analysis. Inhibition of ZFAS1 decreased the apoptotic rate of pORF5 and reduced the infectivity of C. trachomatis, and MAPK/p38 pathway was involved in anti-apoptotic effect induced by ZFAS1. Therefore, the present study confirmed that pORF5 up-regulates ZFAS1 to promote host cell survival via MAPK/p38 pathway and influences the infectivity of C. trachomatis.